MENINGKATKAN PRESTASI BELAJAR MATEMATIKA SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAME TURNAMENT (TGT) - Ahmad, Ahmad; Perwira Negara, Habib Ratu; Ayu Kurniawati, Kiki Riska (LP2M Institut Agama Islam Nurul Hakim, 2022)
The purpose of this study is to improve students' mathematics learning achievement by using a team game tournament (TGT) type of cooperative learning model. Sources of data in this study were students of class VII MTs. Darul Falah Batu Jangkih, totaling 28 people. The research method used is descriptive qualitative classroom action research. From the results of research and discussion, it can be seen that in the first cycle, students have an average value of 72.22 and a classical mastery level of 83.10%. This means that the level of student learning mastery has not been achieved in accordance with the predetermined learning mastery standards. In this cycle, the classical learning completeness did not meet the specified criteria, namely 85%. Based on the results of the second cycle analysis, the average student score was 85.10, and the classical mastery level of students was 95%. This means that student mastery is based on the level of mastery that has been determined in accordance with the provisions that have been determined. Thus, it can be concluded that the TGT type of cooperative learning model can improve student achievement. This happens because in this learning model students are given the opportunity to learn while playing, learn to discuss groups, ask questions, make conclusions, share knowledge by guiding members. the group if there are those who do not understand the material well and students are also not shy to ask questions and discuss with the teacher during the group guidance procession.